Terapi Bekam Terhadap Tingkat Nyeri pada Pasien Hipertensi di Wilayah Pesisir : Studi Kasus - Sartiya Rini, Dewi; Muhsina, Sitti; Sari, Puput Novita (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Pain is a common complaint most often complained by people with hypertension. One of the non-pharmacological therapies that can be used to reduce pain levels in hypertensive patients is Cupping therapy. Cupping is a method of treatment by removing metabolic waste blood or blood contaminated with toxins and oxidants from the body through the surface of the skin. This study aims to determine the picture of the application of cupping therapy to pain levels in hypertensive patients in the coastal area of Kendari City. Method: This research design uses a descriptive case study approach, the subject in this study is one case study subject with a medical diagnosis of hypertension aged between 35-50 years, no blood clotting disorder, no history of heart disease, stroke and no history of seizures. Results: The application of cupping therapy carried out on case study subjects showed a change in pain levels characterized by complaints of pain and decreased blood pressure. The initial pain scale shows a scale of 6 (moderate pain) and decreases to a scale of 2 (mild pain). Blood pressure measurements showed systolic blood pressure of 143 mmHg to 123 mmHg and diastolic 90 mmHg to 80 mmHg. Suggestion: Cupping therapy is one of the complementary therapies that can be used by nurses in patients with hypertension.